Traversing the fantasy: why leftist academics must abandon the myth of organic resistance and think again about the problems we face - Kelly, Emma (Critical criminology, 2022)
The concept of organic resistance has stood as a cornerstone of critical social science for decades. Countless authors have claimed that minor acts of "transgression" should be interpreted as indicators of a proto-revolutionary drive among the marginalized to fight oppressive power. Here, we argue that critical scholars must jettison such baseless idealism and accept the huge amount of work needed to create within people a desire for genuine change. Post-1968 liberal capitalism has proven itself, time and again, able to integrate dissent and dissatisfaction into its project of continuous self-revolution. To move forward, we must accept a regrettable reality: most marginalized citizens dream not of overthrowing the system, but of achieving a degree of security and success within the system as it stands. If critical criminology is to continue to shed new light upon the huge problems we face, the lives of our most marginalized citizens must be represented with a greater degree of honesty.